Does Political Risk Matter for Economic Growth in Cyprus? - Kirikkaleli, Dervis; Kalmaz, Demet Beton (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2024)
This study aims to capture the co-movement between political risk and economic growth in Cyprus employing quarterly data over the time period between 1995Q1 and 2018Q4, adopting a wavelet coherence technique allowing to investigate both the short and long run causal link between economic growth and political risk in Cyprus. The outcomes obtained expose that (i) economic growth and political risk were significantly vulnerable in 2000 and 2004 at varying frequencies; (ii) political risk was an important factor for predicting economic growth in Cyprus between 2006 and 2018; (iii) economic growth causes political risk in Cyprus in the short term between 2006 and 2009. In addition, it is noteworthy that causality tests of gradual–shift and Toda-Yamamoto are utilized to verify the significance of political risk for predicting economic growth in Cyprus.